Analysis of Gamification Implementation in E-Learning Models on the Psychology of Engineering Major Students - Sofyan, Vina Annisa; Rosidah; Andi Dio Nurul Awalia; Putri Fariza; Annajmi Rauf; Elma Nurjannah (Fakultas Teknik, Universitas Negeri Makassar, 2025)
Gamification is one of the learning strategies in education that can increase students’ interest and motivation in the learning process. The application of gamification is implemented in the E-learning model. In general, students do not enjoy repetitive tasks over long periods of time, yet they are willing to spend a considerable amount of time playing games. This study aims to understand the psychology of students regarding the implementation of gamification across all Engineering Departments at Universitas Negeri Makassar. This descriptive research model was conducted to examine students’ responses after its implementation. Students from Universitas Negeri Makassar in all Engineering Departments participated using a Google Form questionnaire with 15 statements as the data collection method. Data were obtained through a Likert Scale and analyzed using qualitative descriptive statistics. This analysis was intended to describe the characteristics of each variable. The results of this study indicate that the implementation of gamification in E-learning can enhance students’ active learning performance and has a significant impact on the psychology of each student.